Understanding the Characteristics of Muhkam and Mutashabih Verses Through the Twentieth Principle in al-Qawā‘id al-Ḥisān by Abdurrahman al-Sa‘dī - Safira Nur Arifah; Mohammad Athoillah; Ali Khosim (Program Magister Ilmu Al-Qur'an dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2025)
Understanding of the Qur’an can be achieved through mastery of the various disciplines encompassed within ʿulūm al-Qur’ān, one of which is the branch of knowledge that discusses the muhkam and mutashabih verses. This study aims to elaborate more deeply on the characteristics of muhkam and mutashabih verses by referring to the twentieth principle in al-Qawā‘id al-Ḥisān fī Tafsīr al-Qur’ān by Abdurrahman al-Sa‘dī. Using a qualitative-descriptive approach based on library research, the twentieth principle in al-Qawā‘id al-Ḥisān maps verses into three categories: entirely muhkam, entirely mutashabih, and verses that contain elements of both muhkam and mutashabih to a certain degree. The results of the study indicate that muhkam verses possess several main characteristics: their meanings are clear and their intent can be understood; they do not require interpretation (ta’wil); they can stand independently without reliance on other verses; their wording is not repetitive; and they contain legal provisions such as commands, promises, and threats. As for mutashabih verses, their characteristics are as follows: some of their meanings cannot be fully comprehended by human beings and their ultimate knowledge rests only with Allah SWT, such as the occurrence of the Day of Judgment; others can be understood through interpretation and in-depth study; they require ta’wil; they cannot stand independently without reference to other verses; their wording tends to be repetitive; and they often contain narratives and parables